Improvement of productivity and quality of entrepreneur Bika Bakar in Medan city - Hutagalung, Arif qaedi; Sianipar, Aryanti Sariartha; Dalimunthe, Doli Muhammad Jafar (Talenta Publisher, 2020)
In Community Service activities, partners are Bika Bakar business actors in Medan City. The business partner has been engaged in the culinary sector, especially traditional cake type foods since 1990. The type of cake food produced by this business partner is baked bika cake. The production process is carried out at home with the help of several employees and equipment that is still simple, does not have accountancy , packaging that still uses plastic bags and limited access to marketing. Promotions that are lacking make partner products unable to compete with cake products produced by large businesses. Partners still use simple tools so that the production of bika bakar is not optimal in quantity and quality of production, so that Ms. Nurmalis' roasted bika is still less popular than cakes with well-known brands. Improvement in designing good simple bookkeeping in financial management. Increasing the quality and quantity of Bika Bakar production after the addition of a furnace and an increasing number of bika cake molds and using good paper bags, as well as product development through making brands in Bika Bakar Mitra products and online marketing.